Проблема гострого порушення мозкового кровообігу з точки зору лікаря-інтенсивіста - Полінчук, І.С.; Туряниця, С.В.; Малахов, П.С.; Цимбал, Ю.Ф.; Арбузова, В.А.; Сидорко, Ю.В. (Актуальні проблеми транспортної медицини, 2007)
Острое нарушение мозгового кровообращения (ОНМК) — одна из самых острых медико-социальных проблем современного общества. При этой патологии внезапно изменяется качество жизни человека: от активного члена общества до инвалида, а с экономической точки зрения, с плательщика налогов до человека, требующего помощи государства. В связи с этим рассмотрены блоки организационных, методических, медико-социальных и финансовых проблем, которые существуют в реабилитации этого контингента пациентов на примере общегородского инсультного центра при Клинической больнице Суворовского района г. Херсона. Acute disorders of brain blood circulation (insult) is one of most medical and social problems of modern society. At this pathology quality of life of man changes suddenly. Among people which get the group of disability first the every fourth is that, who carried an insult. Only about 20% people after an insult go back to an own profession. In our state annually registered from 120 to 175 thousand of incidents of acute disorders of brain blood circulation. For today in Ukraine lives about 1 million persons which carried an insult. About 80% from them is invalids. With the purpose of improvement of quality of life of patients after insult and increase of efficiency of medical process, on the base of clinical hospital of the Suvorov’s district of Kherson, from 01.01.2006 year was opened a city insult’s center on 55 beds. In the article work of department of anesteziology and intensive care is analyzed in the conditions of functioning of insult’s center. The ways of working out basic problems are set.